Assessing reported cases of sexual and gender-based violence, causes and preventive strategies, in European asylum reception facilities - Charlotte Oliveira; Ines Keygnaert; Maria do Rosário Oliveira Martins; Sónia Dias (BMC, 2018)
Abstract Background Sexual and gender-based violence (SGBV) is a widespread public health problem and a violation of human rights rooted in gender and power inequities. Refugees, asylum-seekers and migrants living in European asylum reception facilities (EARF) are especially vulnerable to SGBV. To contribute to closing the gap on systematic and accurate evidence on SGBV, we aim to explore reported cases of SGBV, causes and preventable measures described by residents and professionals from EARF. Methods We developed a cross-sectional study using the Senperforto project database. Semi-structured interviews were conducted with residents (refugees, asylum-seekers and unaccompanied minors) and professionals (service and health care providers) at EARF, in 7 European countries. We used IBM® SPSS software to analyze our data. Further, statistical tests - Chi-square Test and Fisher's exact test (5% significance level) were conducted. Results In total 562 respondents: 375 residents (R) and 187 professionals (P) participated in the study. The majority of respondents were male (56.9%), aged 19 to 39 years (67.3%). Respondents described 698 cases of SGBV (R 328, P 370), comprising 1110 acts of multi-types of violence. Respondents from Malta (160) and Belgium (143) reported the highest number of SGBV cases. The main reported causes were frustration and stress (R 23.6%, P 37.6%, p 0.008) and differences related with cultural background (R 19.3%, P 20.3%, p 0.884). Respondents assumed that these acts of violence could be prevented by SGBV prevention interventions (R 31.5%, P 24.7%, p 0.293); improving living conditions (R 21.7%, P 15.3%, p 0.232); and promoting communication (R 16.1%, P 28.2%, p 0.042). The majority of R were not aware of existing preventable measures in the asylum facility or host country. While the majority of P were aware of existing preventable measures in the asylum facility or country. Proposed SGBV prevention strategies in EARF included SGBV sensitization and awareness, improving living conditions and improving communication between R and P. Conclusion In the EARF context, SGBV is characterized by multi-types of violence acts, yet R and P believe that prevention is possible. Our results call for urgent integrative prevention strategies that are in line with country-level and international regulations.